2001
DOI: 10.1143/jjap.40.5999
|View full text |Cite
|
Sign up to set email alerts
|

New High Temperature Morphotropic Phase Boundary Piezoelectrics Based on Bi(Me)O3–PbTiO3 Ceramics

Abstract: New morphotropic phase boundary (MPB) piezoelectrics, with ferroelectric phase transition (T c ) exceeding that of PbZrO 3 -PbTiO 3 (PZT), were investigated. Based on a perovskite tolerance factor-T c relationship, new high T c MPB systems were projected in the Bi(Me)O 3 -PbTiO 3 system, where Me is a relatively large B +3 -site cation. For the (1 − x)BiScO 3 -(x)PbTiO 3 solid solution, a MPB was found at x-0.64 separating the rhombohedral and tetragonal phases, with correspondingly enhanced dielectric and pie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
537
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 830 publications
(581 citation statements)
references
References 11 publications
25
537
1
2
Order By: Relevance
“…9, the T max of 85PZN-5PT-10RN ͑100-105°C͒ was higher than that of 85PZN-5PT-10BT ͑53°C͒. 4 T max increased and the dielectric dispersion with the measuring frequency decreased with increasing the PT content. These observations were more pronounced in PZN-PT-NN, which can be explained as following.…”
Section: B Change In the Mpb Of The Ternary Systemsmentioning
confidence: 81%
See 2 more Smart Citations
“…9, the T max of 85PZN-5PT-10RN ͑100-105°C͒ was higher than that of 85PZN-5PT-10BT ͑53°C͒. 4 T max increased and the dielectric dispersion with the measuring frequency decreased with increasing the PT content. These observations were more pronounced in PZN-PT-NN, which can be explained as following.…”
Section: B Change In the Mpb Of The Ternary Systemsmentioning
confidence: 81%
“…When the PT makes the solid solution, the lower tolerance factor of the counterpart material increases the T max at the MPB. 5,20 Combined experiments with the first principle calculations on Pb based solid solutions have shown that T max is proportional to the square of Pb and B-cation displacement since coupling between nearest-neighboring ferroelectrically active cations increases. 21,22 Small tolerance values indicate that the cations partially fill an A site and there is an empty space in the A site, as shown in Eq.…”
Section: B Change In the Mpb Of The Ternary Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Керамика твердых растворов (1 − x)BiScO 3 · xPbTiO 3 (BS−PT) со структурой перовскита с составами близкими к морфотропной фазовой границе (МФГ) между их ромбоэдрической и тетрагональной фаза-ми (x = 0.64), характеризуется пьезомодулями d 33 ∼ ∼ 400 pC/N [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], сопоставимыми по величине с пьезо-модулями цирконата-титаната свинца (ЦTС) -широко используемой пьезокерамики [17][18][19]. При этом точка Кюри керамики BS−PT (T c ∼ 720 K) превышает T c ЦТС на ∼ 100 K, что позволяет повысить температурный диапазон ее использования.…”
Section: Introductionunclassified
“…15,16 Recently, a qualitative relationship between perovskite tolerance factor and the Curie point ͑T c ͒ at the MPB in PbTiO 3 based systems was proposed. 11,[17][18][19] In general, the smaller the tolerance factor of the non-PbTiO 3 end member, the higher T c at the MPB. 14,20 Guided by this relationship, low tolerance factor bismuth perovskite compounds with PbTiO 3 have been shown to be promising candidates for new, lead-free or lead reduced, high T m RFEs.…”
Section: Introductionmentioning
confidence: 99%